Physiological and metabolic adaptations of Potamogeton pectinatus L. tubers support rapid elongation of stem tissue in the absence of oxygen. - Dixon, M; Hill, SA; Jackson, M; Ratcliffe, R; Sweetlove, L (2006)
Tubers of Potamogeton pectinatus L., an aquatic pondweed, over-winter in the anoxic sediments of rivers, lakes and marshes. Growth of the pre-formed shoot that emerges from the tuber is remarkably tolerant to anoxia, with elongation of the stem occurring faster when oxygen is absent. This response, which allows the shoot to reach oxygenated waters, occurs despite a 69-81% reduction in the rate of ATP production, and it is underpinned by several physiological and metabolic adaptations that contribute to efficient energy usage. First, extension of the pre-formed shoot is the result of cell expansion, without the accumulation of new cellular material. Secondly, after over-wintering, the tuber and pre-formed shoot have the enzymes necessary for a rapid fermentative response at the onset of growth under anoxia. Thirdly, the incorporation of [(35)S]methionine into protein is greatly reduced under anoxia. The majority of the anoxically synthesized proteins differ from those in aerobically grown tissue, implying an extensive redirection of protein synthesis under anoxia. Finally, anoxia-induced cytoplasmic acidosis is prevented to an unprecedented degree. The adaptations of this anoxia-tolerant plant tissue emphasize the importance of the mechanisms that balance ATP production and consumption in the absence of oxygen.